The Decentralization of Public Employment Services and Local Governments’ Responses to Incentives - Nieminen Jeremias; Kanninen Ohto; Karhunen Hannu (Oxford University Press, 2025)
We examine how the decentralization of public employment services (PES) affects the behavior and service provision of PES offices and the labor market outcomes of job seekers. We use difference-in-differences, utilizing a Finnish temporary reform during which PES were decentralized for specific groups of job seekers in treated municipalities and remained centralized for others. The reform presented the treated municipalities with the possibility of shifting costs to the central government. We find no evidence of better labor market outcomes and find evidence consistent with municipalities being able to shift 10% of their unemployment benefit costs to the central government.